Foreign Direct Investment, Economic Growth and Financial Sector Development in Small Open Developing Economies (2012)
The present paper examines the causal linkage between foreign direct investment (FDI) and economic growth - in Cote d'Ivoire, Gambia, Ghana, Nigeria and Sierra Leone - with financial development accounted for over the period 1970-2005 within a trivariate framework which applies Granger causality tests in a vector error correction (VEC) setting. Three alternative measures of financial sector development - total liquid liabilities, total banking sector credit and credit to the private sector - were employed to capture different ramifications of financial intermediation. Our results support the view that the extent of financial sophistication matters for the benefits of foreign direct investment to register on economic growth in Ghana, Gambia and Sierra Leone depending on the financial indicator used. Nigeria, on the other hand, displays no evidence of any short- or long-run causal flow from FDI to growth with financial deepening accompanying. In sum, therefore, what should be of utmost urgency is concerted efforts in most of these countries, which have typically been in the throes of economic reforms, to upgrade their financial structure to better position them to reap the desirable growth promoting effects of FDI flows.